DEEP MARKETING MIX STRATEGY INCREASING BANANA SALE SALES VOLUME (Case Study on Sari Murni Olamin Agroindustry in Bangunreja Village Kedungreja District, Cilacap Regency) - Suryati, Suryati; Sudrajat, Sudrajat; Aziz, Saepul (Jurnal Ilmiah Mahasiswa AGROINFO GALUH, 2024)
factors affect the agroindustry of Sari Murni Olapis banana sale, 2) External factors affect the agroindustry of Sari Murni Olapis banana sale, 3) Marketing mix strategy to increase the sales volume of banana sales in the Sari Murni Olapis agroindustry. This research uses the case study method. Data analysis used using SWOT Analysis, SWOT Matrix, SWOT Diagram and Marketing Mix (4P). The results of this study show internal factors in the form of strategic location, complete licensing, available labor, packaging of various sizes as needed, affordable prices for the wider community, raw materials for banana sale are easily damaged or rotten, products are easily expired, the facilities and advice used are still simple, the promotions carried out have not been optimal. External factors include product variations, promotions and advertisements can still be maximized, have good market opportunities or broad market share, the emergence of new competitors, rising raw material prices, many new types of food. The marketing mix strategy used is marketing mix product, price, place and promotion.   Keywords: Banana, Banana Sale, SWOT, SWOT matrix, SWOT diagram, maketing mix.